Hypertension in Thyroid Disorders - Berta, Eszter; Lengyel, Inez; Halmi, Sándor; Zrínyi, Miklós; Erdei, Annamária; Harangi, Mariann; Páll, Dénes; Nagy, Endre V.; Bodor, Miklós (Frontiers in Endocrinology, 2019)
Arterial hypertension represents a major global health concern; more than one fourth of the population is affected by high blood pressure. Albeit the underlying cause of the disease remains unclear in the vast majority of the cases, approximately ten percent are of secondary origin. Endocrine disorders are common illnesses and some of them may lead to elevated blood pressure, among which thyroid diseases are of high prevalence and often overlooked, especially in mild cases. Overt and subclinical hyper- and hypothyroidism can both lead to (mostly mild) hypertension; however, the underlying mechanisms are only partially understood. The results of clinical studies are often controversial. During the past decades, some genetic mutations in the hypothalamus-pituitary-thyroid axis with cardiovascular consequences were revealed. Atherosclerotic changes resulting from lipid abnormalities due to thyroid dysfunction also affect the vasculature and can cause elevated blood pressure. The review gives a synopsis of our knowledge how thyroid hormone metabolism and functional thyroid diseases affect the cardiovascular system, their negative impact and causative role in the development of hypertension.